The N-Terminal Flanking Region of the Invariant Chain Peptide Augments the Immunogenicity of a Cryptic “Self” Epitope from a Tumor-Associated Antigen - Hess, A.D.; Thoburn, C.; Chen, W.; Miura, Y.; Wall, E. van der (Academic Press, 2001)
The N-terminal flanking region of the invariant chain peptide termed CLIP appears to have superagonistic properties interacting with the T cell receptor and the MHC class II molecule at or near the binding site for the bacterial superantigen Staphylococcal enterotoxin B (SEB). The present studies explored the hypothesis that the N-terminal segment of CLIP can augment the immunogenicity of cryptic “self” tumorassociated antigens. A chimeric construct of an MHC class II binding peptide from the c-erb oncogene (Her-2/neu) containing the N-terminal flanking region of CLIP elicited potent antitumor activity against a Her-2/neu-positive tumor in a rat model system. Comparatively, the unmodified parent peptide was ineffective. The induction of effective antitumor immunity, however, required presentation of the chimeric peptide construct on irradiated tumor cells or the peptide construct in concert with a Her-2/neu MHC class I-restricted peptide from Her-2/neu. As revealed by adoptive transfer studies, effective protective antitumor immunity in this setting required the CD4 T helper subset. Additionally, in vitro analysis revealed that immunization with the parent peptide resulted in a weak immune response to the unmodified peptide consisting of both type 1 (IL-2, IFN-g) and type 2 (IL-4, IL-10) cytokine-producing cells analyzed by RT–PCR (qualitative and quantitative) and by limiting dilution assay. Comparatively, immunization with the chimeric construct elicited a potent immune response to the parent peptide with predominantly type 1 cytokine-producing cells. Taken together, the results suggest that immunization with the chimeric Her-2/neu peptide induced protective antitumor immunity. Associated with this immunization strategy was the enhancement of a type 1 cytokine response.
Keywords: Geneeskunde; tumor vaccine; invariant chain peptide; modified Her-2/neu peptide